Madam Kitchens feeding with Iman - Mhd. Sarif, Suhaimi; Hidayatullah, Rakhmad Agung; Firmansah, Yayan (IIUM Press, 2025)
The Pondok system represents a unique model of Islamic education that seamlessly integrates academics, spirituality, and communal living. This traditional yet dynamic approach fosters intellectual, moral, and spiritual growth within a shared environment, where students and teachers live and learn together. At its core, the Pondok emphasizes discipline, collaboration, and the development of Islamic values such as ta’awun (cooperation) and ukhuwwah (brotherhood). A structured daily routine includes Quranic memorization, traditional Islamic sciences, and character-building activities, balanced with physical recreation and community service. The katibah system instills leadership and accountability through night patrols, while the meal preparation system, managed by Madams, Kitchen Managers, and student helpers, serves as a practical training ground in entrepreneurship, logistics, and teamwork. Weekly coordination meetings further reinforce operational excellence, sustainability, and entrepreneurial innovation to meet the needs of students in a resource-conscious system. This case study explores how the Pondok system creates a nurturing and resilient educational community, instilling lifelong values and preparing students for meaningful contributions to society.